Tracking the impact of depression in a perspective-taking task - Heather J. Ferguson (Nature Portfolio, 2017)
Abstract Research has identified impairments in Theory of Mind (ToM) abilities in depressed patients, particularly in relation to tasks involving empathetic responses and belief reasoning. We aimed to build on this research by exploring the relationship between depressed mood and cognitive ToM, specifically visual perspective-taking ability. High and low depressed participants were eye-tracked as they completed a perspective-taking task, in which they followed the instructions of a ‘director’ to move target objects (e.g. a “teapot with spots on”) around a grid, in the presence of a temporarily-ambiguous competitor object (e.g. a “teapot with stars on”). Importantly, some of the objects in the grid were occluded from the director’s (but not the participant’s) view. Results revealed no group-based difference in participants’ ability to use perspective cues to identify the target object. All participants were faster to select the target object when the competitor was only available to the participant, compared to when the competitor was mutually available to the participant and director. Eye-tracking measures supported this pattern, revealing that perspective directed participants’ visual search immediately upon hearing the ambiguous object’s name (e.g. “teapot”). We discuss how these results fit with previous studies that have shown a negative relationship between depression and ToM.